Delimitacja systemów gospodarczych w naukach ekonomicznych - Gorynia, Marian (Wydział Prawa i Administracji UAM, 1993)
The article presents methodic aspects of distinguishing economic systems as a subject-matter of economic sciences. The delimitation of economic systems may be carried out by means of the conception of hierarchical structure and order. The delimitation of economic systems should be performed on two planes: vertical and horizontal. A vertical plane is connected with the determination of hierarchical level, i.e., the level of the analysis of social existence. In turn, a horizontal plane is connected with the criteria of subordination of sub-systems distinguished at a given level of analysis. The traditional economy distinguished two levels of analysis: micro and macro. In the 20th c. three additional levels of analysis have been distinguished: micromicro, mezo and global. The article discusses the characteristics of analyses conducted at particular levels. The last part of t he article contains the examples of delimitation of economic sub-systems in four branches of economy: (i) theory of industry organization; (ii) regional economy and zoning; (iii) organization and management, and (iv) marketing.
Delimitation of economic systems in economic sciences